Enhancement of mitochondrial ATP production by the Escherichia coli cytotoxic necrotizing factor 1. (1st July 2014) - Travaglione, Sara; Loizzo, Stefano; Rizza, Teresa; Del Brocco, Antonella; Ballan, Giulia; Guidotti, Marco; Vona, Rosa; Di Nottia, Michela; Torraco, Alessandra; Carrozzo, Rosalba; Fiorentini, Carla; Fabbri, Alessia
<x xml:space="preserve">Abstract</x> Mitochondria are dynamic organelles that constantly change shape and structure in response to different stimuli and metabolic demands of the cell. The Escherichia coli protein toxin cytotoxic necrotizing factor 1 (CNF1) has recently been reported to influence mitochondrial activity in a mouse model of Rett syndrome and to increase ATP content in the brain tissue of an Alzheimer's disease mouse model. In the present work, the ability of CNF1 to influence mitochondrial activity was investigated in IEC‐6 normal intestinal crypt cells. In these cells, the toxin was able to induce an increase in cellular ATP content, probably due to an increment of the mitochondrial electron transport chain. In addition, the CNF1‐induced Rho GTPase activity also caused changes in the mitochondrial architecture that mainly consisted in the formation of a complex network of elongated mitochondria. The involvement of the cAMP‐dependent protein kinase A signaling pathway was postulated. Our results demonstrate that CNF1 positively affects mitochondria by bursting their energetic function and modifying their morphology.